Adipose-Derived Stem Cell Transplantation Attenuates Inflammation and Promotes Liver Regeneration after Ischemia-Reperfusion and Hemihepatectomy in Swine - Zhihui Jiao; Yajun Ma; Xiaoning Liu; Yansong Ge; Qianzhen Zhang; Boyang Liu; Hongbin Wang (Stem Cells International)
Aim. To study the anti-inflammatory and liver regenerative effects of adipose-derived mesenchymal stem cells (ADSCs) on a porcine model of ischemia-reperfusion (IR) and hemihepatectomy. Methods. Eighteen healthy Bama miniature pigs were randomly divided into the sham-operated (sham), untreated IR injury (IRI), and ADSC-transplanted (ADSC) groups. Hepatic IR was established by laparoscopic hemihepatectomy. ADSCs were transplanted directly into the liver parenchyma after the surgery. Hepatic inflammation and liver regeneration were evaluated by histopathological examination and assessment of relevant cytokines and other factors. Results. ADSC transplantation successfully ameliorated the IRI-induced histopathological damage and the high levels of pro-inflammatory cytokines like IL-1β, IL-6, and TNF-α. In addition, the ADSCs enhanced the expression of the anti-inflammatory IL-10, regenerative factors including HGF, Cyclin D1, and proliferating cell nuclear antigen (PCNA), and angiogenic factors like VEGF, ANG-1, and ANG-2. Conclusions. ADSCs attenuated the hepatic IRI-induced inflammatory response and promoted liver regeneration.